2021
DOI: 10.3390/w13233463
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Alkaline Earth Metals from Desalination Brine for Carbon Capture and Sodium Removal

Abstract: Because carbon dioxide adsorbs the radiation from the Sun and the Earth’s surface, global warming has become a severe problem in this century. Global warming causes many environmental problems such as heatwave, desertification, and erratic rainfall. Above all, erratic rainfall makes people have insufficient freshwater. To solve this problem, desalination technology has been developed in many countries. Although desalination technology can provide freshwater, it produces brine as well (producing 1 L of freshwat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Overall, results of the Margi (Figure 5) and Galia (Figure 6) precipitation tests confirmed that >99.9% Mg 2+ recovery can be achieved from artificial and real bitterns employing over-stoichiometric NaOH solutions in accordance with data reported in the literature [13,21,25,36].…”
Section: Galia Bitternsupporting
confidence: 87%
See 1 more Smart Citation
“…Overall, results of the Margi (Figure 5) and Galia (Figure 6) precipitation tests confirmed that >99.9% Mg 2+ recovery can be achieved from artificial and real bitterns employing over-stoichiometric NaOH solutions in accordance with data reported in the literature [13,21,25,36].…”
Section: Galia Bitternsupporting
confidence: 87%
“…The brines contained 2.84 g/L of Mg 2+ , which was recovered via precipitation in the form of MH. In the last decade, increasing interest has been placed on seawater desalination [11][12][13] and the high magnesium content in lake brines, as in the case of the Uyuni salar (Bolivia), which is one of the largest sources of lithium and also contains 15-18 g/L of Mg 2+ [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The reactions of using Ca(OH) 2 , KOH, and Al(OH) 3 to conduct the Modified Solvay Process are listed in Equations ( 7) to (9). [63][64][65][66] M. H. El-Naas et al directly added CaO to the bubble column reactor, which converts to calcium hydroxide as soon as it contacts the brine. The results revealed that CO 2 capture of 99% and Na production rate of 35% were achieved under 20 g L −1 of CaO, 10 °C, 13 wt% of NH 4 HCO 3 , and a gas flow rate of 500 mL min −1 .…”
Section: Solvay Process/modified Solvay Processmentioning
confidence: 99%
“…Ca(OH) 2 -based [ 64] 0.6 mol L −1 brine 45% >11 15 °C 1 b a r -KOH-based [ 66] 0.5 g g −1 KOH 45.6% 13.6 50 °C 2 bar 776 mL min −1 KOH-based [ 67] 0.58 g g −1 KOH 44.1% >13 10 °C 2.1 bar 848.5 mL min −1…”
Section: Solvay Process/modified Solvay Processmentioning
confidence: 99%
“…Moreover, extracting metals from brine can assist in achieving the United Nations (UN) sustainable development goals, such as “Clean water and sanitation (SDG 6)” and “Life below water (SDG 14) (Herrera, 2019; Schmidt et al, 2017). ” According to the above narrative, some metals have already been recovered from desalination brine and employed for further application in our former research (Chen et al, 2020; Lee, Chen, & Chen, 2021; Lee, Chen, & Wu, 2021).…”
Section: Introductionmentioning
confidence: 99%